The effect of interface phonons on operating electron states in three-barrier resonant tunneling structure as an active region of quantum cascade detector - Tkach, M.V.; Seti, Ju.O.; Grynyshyn, Y.B.; Voitsekhivska, O.M. (Condensed Matter Physics, 2014)
The Hamiltonian of electrons interacting with interface phonons in three-barrier resonant tunneling structure is established using the first principles within the models of effective mass and polarization continuum. Using the Green's functions method, the temperature shifts and decay rates of operating electron states are calculated depending on geometric design of three-barrier nano-structure GaAs/AlxGa₁₋xAs which is an active region of quantum cascade detector. It is established that independently of the temperature, the energy of quantum transition during the process of electromagnetic field absorption is a nonlinear weakly varying function of the position of the inner barrier with respect to the outer barriers of the structure. З перших принципiв у моделi ефективних мас та поляризацiйного континууму встановлено гамiльтонiан системи електронiв взаємодiючих з iнтерфейсними фононами у трибар’єрнiй резонансно-тунельнiй
структурi. Методом функцiй Грiна розраховано температурнi змiщення й загасання найнижчих (робочих)
електронних станiв у залежностi вiд геометричної конфiгурацiї наносистеми GaAs/ AlxGa₁₋xAs як активної зони квантового каскадного детектора. Встановлено, що незалежно вiд температури системи енергiя
квантового переходу в процесах поглинання електромагнiтного поля є нелiнiйною слабозмiнною функцiєю вiд положення внутрiшнього вiдносно зовнiшнiх бар’єра наносистеми.